Sand smelt ability to cope and recover from ocean's elevated CO 2 levels - Silva, Cátia S. E. (2018)
Considered a major environmental concern, ocean acidification has induced a recent research boost into effects on marine biodiversity and possible ecological, physiological, and behavioural impacts. Although the majority of literature indicate negative effects of future acidification scenarios, most studies are conducted for just a few days or weeks, which may be insufficient to detect the capacity of an organism to adjust to environmental changes through phenotypic plasticity. Here, the effects and the capacity of sand smelt larvae Atherina presbyter to cope and recover (through a treatment combination strategy) from short (15 days) and long-term exposure (45 days) to increasing pCO2 levels (control: ~515 μatm, pH = 8.07; medium: ~940 μatm, pH = 7.84; high: ~1500 μatm, pH = 7.66) were measured, addressing larval development traits, behavioural lateralization, and biochemical biomarkers related with oxidative stress and damage, and energy metabolism and reserves. Although behavioural lateralization was not affected by high pCO2 exposure, morphometric changes, energetic costs, and oxidative stress damage were impacted differently through different exposures periods. Generally, short-time exposures led to different responses to either medium or high pCO2 levels (e.g. development, cellular metabolism, or damage), while on the long-term the response patterns tend to become similar between them, with both acidification scenarios inducing DNA damage and tending to lower growth rates. Additionally, when organisms were transferred to lower acidified condition, they were not able to recover from the mentioned DNA damage impacts. Overall, results suggest that exposure to future ocean acidification scenarios can induce sublethal effects on early life-stages of fish, but effects are dependent on duration of exposure, and are likely not reversible. Furthermore, to improve our understanding on species sensitivity and adaptation strategies, results reinforce the need to use multiple biological endpoints when assessing the effects of ocean acidification on marine organisms.